Investigation of terrain slope effects on wind enhancement by a line source fire. (September 2019) - Eftekharian, E.; Ghodrat, M.; He, Y.; Ong, R.H.; Kwok, K.C.S.; Zhao, M.; Samali, B.
Abstract: Wind enhancement triggered by fire-wind interaction can potentially pose significant damage to structures built in bushfire prone areas. The effect of terrain slope is one of the parameters contributing to the enhancement of wind by fire that needs to be taken into account. This study employs a validated model of Computational Fluid Dynamics to assess the effects of terrain slope on this phenomenon. A module was developed and appended to the FireFOAM solver to output individual component of flow acceleration. Multiple analyses were used to explain the effects of terrain upslope and downslope on the phenomenon. The results reveal that although the enhancement of wind velocity due to fire increases with an increase in terrain upslope, a terrain downslope reduces flow enhancement by fire. The results also established that while an upslope terrain reinforces the Coanda effects and intensifies attachment of the plume to the ground, the downslope condition mitigates Coanda effects and reduces the flow's tendency to attach to the ground downstream of the fire source. Furthermore, under a constant heat release rate and upstream wind velocity, the maximum magnitude of wind enhancement linearly increases with the increase of upslope angle.